Universal health coverage in India: Newer innovations and the role of public health - Suneela Garg (Wolters Kluwer Medknow Publications, 2018)
The realization of Universal Health Coverage requires adequate healthcare financing and human resources to provide financial protection to the economically disadvantaged population by covering their medicine, diagnostics, and service costs. Conventionally, inadequate public healthcare financing and the lack of skilled human resources are considered as the major barriers towards achieving UHC in India. To strengthen the Indian healthcare system, there has been significant increase budgetary allocation towards healthcare, a national health protection scheme targeting low-income households, upgrading of primary health-care and expansion of the health work-force. Nevertheless, an evolving paradigm for improving holistic health, sanitation, nutrition, gender equity, drug accessibility and affordability, innovative initiatives in national health programs for reduction of maternal deaths, tuberculosis and HIV burden and the utilization of information technology in healthcare provision of the underserved and the marginalized is gaining rapid acceleration. These represent a genuine innovation towards fulfillment of UHC goals for India.